A clinical case of primary membranous glomerulonephritis with nephrotic syndrome and resistance to standard treatment - Denova, L.D.; Krasiuk, I.V. (KIDNEYS, 2023)
The incidence of primary membranous glomerulonephritis is 1 case per 100,000 each year (75–80 %), with a male-to-female ratio of 2 : 1. It is the cause of idiopathic nephrotic syndrome in more than 20 % of cases (over 40 % in people aged 60 and older). The problem of membranous glomerulonephritis consists in a difficult differential diagnostic search and frequent cases of resistance to treatment. Resistance to treatment may develop in 10–20 % of patients, resulting in the end-stage renal disease requiring renal replacement therapy (dialysis or kidney transplantation). Our work presents the results of clinical observation of a patient with primary membranous glomerulonephritis, nephrotic syndrome and resistance to standard treatment. This patient had a positive dynamics of clinical-laboratory-instrumental indicators and an improvement in the quality of life against the background of taking rituximab.